Microwave-assisted synthesis and characterization of SrMoO4 and SrWO4 nanocrystals - Thongtem T. (2014)
SrMoO4 and SrWO4 nanocrystals have been synthesized using Sr(NO3)2 and Na2MeO4 (Me = Mo and W) in ethylene glycol by a microwave irradiation method at 50% of 180 W for 20 min. The product phases were detected using X-ray and selected area electron diffractions. They show the body-centered primitive tetragonal structure with the lattice parameters of a = b = 5.4007 Å and c = 12.0330 Å for SrMoO4, and a = b = 5.4274 Å and c = 11.9241 Å for SrWO4. X-ray diffraction patterns of the products, obtained by simulation using CaRIne version 3.1 program, are in accordance with those of the corresponding experiment and International Centre for Diffraction Data. A transmission electron microscope revealed the presence of nanocrystals composing the products, with their sizes in the ranges of 14-40 and 14-38 nm for SrMoO4 and SrWO4, respectively. Six different vibrations of ν 1(A g), ν 3(B g), ν 3(E g), ν 4(B g), ν 2(A g), and ν f.r.(A g) were detected using a Raman spectrometer, and the ν 3(F 2) antisymmetric stretching and ν 4(F 2) bending modes of [MeO4]2- tetrahedrons using a Fourier transform infrared spectrometer. Photoluminescence emissions of SrMoO4 and SrWO 4, caused by the 1 T 2 → 1 A 1 transition of electrons, were detected at 410 and 418 nm, respectively. © 2009 Springer Science+Business Media B.V.